Analisa Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Menggunakan Metode Importance Performance Analysis Pada E-Wallet Linkaja Di Kota Yogyakarta - Fathoni, Rahmat; Kurniawan, Hari; Iswandari, Lucia (Green Publisher Indonesia, 2025)
Technological and financial advances in Indonesia have had a significant impact. Intense market competition triggers changes in competition between companies. Linkaja is a digital financial service that was merged between Telkomsel and members of a state-owned enterprise (BUMN), one of the four top-ranked E-wallet platforms in Indonesia. In 2020, Linkaja signed a funding agreement of 100 million in a series B round. However, these funds have not provided good service to ensure customer satisfaction. This study aims to determine the effect of service quality on customer satisfaction provided by the Linkaja E-wallet. This research is a quantitative study; the sample used was 100 Linkaja E-wallet users in the city of Yogyakarta, divided into gender and age groups. While the data analysis technique uses simple linear regression analysis and importance performance analysis, the results of the analysis show that service quality has a positive or significant effect on customer satisfaction given the Linkaja E-wallet. While the results of the importance performance analysis through the calculation of Tki found a total score of 95.99% in this case, indicating that the quality of services provided by the Linkaja E-wallet company has not met consumer satisfaction, Meanwhile, the 12 attribute statements show three attributes that the Linkaja E-wallet must improve, namely attributes regarding promo prices, customer service, and in-app fonts.